Deutsche und niederländische Mystik des Mittelalters: ein Studienbuch - Dinzelbacher, Peter (De Gruyter Studium, 2012)
This volume provides a contemporary overview of texts, images, phenomena and personalities of Christian mysticism during the Western Middle Ages. The material is primarily approached from literary, history of mentality and psychology of religion perspectives. Basic knowledge is communicated through critical analysis and is also made accessible through a glossary. Although this work clearly focuses on German mysticism, developments in other European countries are presented in a comparative manner